KAJIAN SEMIOTIK KULTURAL PERIBAHASA (SESENGGAQ) SASAK - Dian Aprilia Diniarti (Center of Language and Cultural Studies, 2017)
This study investigates the form and meaning of Sasak proverbs. This study used qualitative approach, relying on semiotic analysis from Roland. Subjects of the study were 7 people of East Lombok at the age of 40 years. Data were collected through observation and interview. The study revealed that proverbs in Sasak language have their forms and meaning. Nine kinds of form were identified in this study and the meaning indicated denotative and connotative meaning. The forms were constructed in terms of: syntax, noun phrase, verbal phrase, and adjectival phrase. In addition, meaning of the proverb covered sign.